Asuhan Keperawatan Keluarga Tahap Kelahiran Anak Pertama Pada Keluarga Tn. D Dengan Masalah Gizi Kurang Pada Balita An. A Di Desa Rempoah - Anggraini Dwi Larasati; Arif Nur Hidayanto; Madyo Maryoto (CV. Ulil Albab Corp, 2022)
Toddler nutrition is an important thing that every parent should know. Efforts to improve/improve nutrition can be done by meeting the nutritional needs of children, one of which is through Supplementary Feeding (PMT). The use of Moringa as an additional food source is one source of protein that can be used in an effort to overcome malnutrition. This study used a descriptive design in the form of a case study approach to nursing practice. The case study in this study examines the inability of families to recognize the health problems of family members who suffer from malnutrition by conducting health education related to the effective use of Moringa leaves for 3 x 24 hours. The results showed that the problems that occurred to the client could be resolved on the 3rd day and which was marked by Mr.'s family. D already knows how to meet the nutritional needs of her child, knows how to increase nutritional intake by using Moringa leaves, Mrs. F already knows how to make food from Moringa leaves and Mrs. F can practice how to make food intake from Moringa leaves. Nursing actions by conducting health education related to the use of Moringa leaves can increase family knowledge about nutritional needs in children.